Comparison of the Effects of Ketorolac to Acetaminophen when adder to Lidocaine for Intravenous Regional Anesthesia - Rafia Tabassum, Muhammad Saieh, Badaruddin (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2013)
Background and Objective: This study was done to compare the effect of ketorolac and acetaminophen on pain relief during intravenous regional anaesthesia (IVRA).The objective of the study was to evaluate the likely benefits of addition of ketorolac and acetaminophen to lidocaine in intravenous regional anaesthesia in terms of onset and duration of tourniquet pain and also for analgesic requirement in postoperative period. Method: Hundred patients undergoing hand or forearm surgery received IVRA were assigned in to two groups: Group I received 0.5% lidocaine diluted with 0.9% normal saline plus ketorolac 30 mg made up to a total volume of 40 ml (n = 50), Group II received 0.5% lidocaine diluted with intravenous acetaminophen 300 mg to a total volume of 40 ml ( n = 50). Tourniquet pain onset time, which was defined as the time from tourniquet application to Tramadol administration for relieving tourniquet pain and amount of analgesic consumption during surgery were recorded. Following deflation of tourniquet, postoperative pain and quantity of analgesic uses in post-anesthesia care unit were assessed. Results: Tourniquet pain onset time, postoperative pain and analgesic consumption were same in Group I as compared to Group II (P < 0.001). Conclusions: The addition of ketorolac and acetaminophen to lidocaine for IVRA delays tourniquet pain onset time. Both acetaminophen and ketorolac reduce postoperative pain and analgesic consumption.